2015
DOI: 10.2739/kurumemedj.ms64004
|View full text |Cite
|
Sign up to set email alerts
|

Regular Tooth Brushing is Associated with a Decreased Risk of Metabolic Syndrome According to a Medical Check-Up Database

Abstract: Associations have been reported between periodontal disease and increased cardiovascular disease risk, as well as between healthy self-reported tooth brushing behavior and reduced cardiovascular disease risk. We examined the association between self-reported tooth brushing behavior and the risk of metabolic syndrome (MetS) using a large medical check-up database. A total of 12,548 medical checkup records from a medical screening center in a city in southwest Japan were assessed. Subjects were aged 30 to 59 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The relationship between systemic diseases and self-care activities favoring oral health and hygiene may thus be influenced by other lifestyle behaviors. [ 27 ] Our study found that people suffering from a systemic disease reduced the frequency of tooth brushing. Therefore, from a public health perspective, improving tooth brushing habits is conducive not only to preventing the most generalized dental diseases, but also, and more importantly, to reducing common risk factors for the principal non-communicable diseases.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The relationship between systemic diseases and self-care activities favoring oral health and hygiene may thus be influenced by other lifestyle behaviors. [ 27 ] Our study found that people suffering from a systemic disease reduced the frequency of tooth brushing. Therefore, from a public health perspective, improving tooth brushing habits is conducive not only to preventing the most generalized dental diseases, but also, and more importantly, to reducing common risk factors for the principal non-communicable diseases.…”
Section: Discussionmentioning
confidence: 84%
“…Various studies have shown an association between tooth brushing and a reduced risk of chronic diseases. [ 27 31 ] A number of theories have posited that various aspects of lifestyle behavior are interrelated. The relationship between systemic diseases and self-care activities favoring oral health and hygiene may thus be influenced by other lifestyle behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies reported strong correlations between toothbrushing frequency and metabolic syndrome, hemodialysis [ 38 , 39 , 40 ], or cerebral strokes [ 5 ]. The incidence of hospital-acquired pneumonia, which is frequently associated with plaque or oral debris [ 8 ], declined in nonventilated patients who performed oral hygiene [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Six studies reported oral hygiene status, six studies reported tooth-brushing frequency, two studies reported interdental cleaning, and one study reported dental visits as study factors. In the meta-analysis, a study by Tsutsumi et al [43] was treated as two separate studies, as it reported the results independently for males and females instead of total samples. A similar approach was applied to a study by Kim et al [44], as it provided separate data on interdental brushing and flossing.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%